2020
DOI: 10.21203/rs.3.rs-29457/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rural-urban disparities and factors associated with delayed care-seeking and testing for malaria before medication use by mothers of under-five children, Igabi LGA, Kaduna Nigeria

Abstract: Background Fever in under-five children (U5) is the commonest presenting complaint in general practice and mothers’ recognition is an entry point for fever treatment, including malaria. This study describes rural-urban disparity in fever prevalence in U5, mothers’ malaria knowledge, care-seeking, testing for malaria before antimalaria medication and the associated factors.Methods A cross-sectional survey was conducted among 630 mother-child pairs (rural (300) and urban (330)) selected randomly using a multi-st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…21 These types of healthcare service providers commonly practice presumptive malaria treatment or prescribe unrecommended drugs. [22][23][24] Other reasons could be attributed to self-treatment at home. 23,24 However, more exploration is needed into these patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 These types of healthcare service providers commonly practice presumptive malaria treatment or prescribe unrecommended drugs. [22][23][24] Other reasons could be attributed to self-treatment at home. 23,24 However, more exploration is needed into these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Other reasons could be attributed to self-treatment at home. 23,24 However, more exploration is needed into these patterns. In addition, the country was highly significant in the model.…”
Section: Discussionmentioning
confidence: 99%
“…This study discovered a high prevalence of self-medication for childhood febrile illnesses, with a quarter of the participants administering drugs to children for self-diagnosed illnesses in the previous weeks; this is consistent with reports by Iribhogbe et al 17 and Omale et al, 6 both from Nigeria, that many caregivers selfmedicate for fever before presentation in health facilities. Similarly, Babalola et al 5 reported a high prevalence (33.5%) of home treatment for under-five children with fever in Kaduna, north-west Nigeria. Again, in their surveys, Mensah et al 18 Ghana and Bogale et al 19 in Ethiopia found a high prevalence of self-medication, 40.8% and 67.3%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, poor health-seeking behavior, such as delayed presentation to health facilities and self-treatment at home, is prevalent in our environment. 5,27,29 In our setting, this is a significant contributor to childhood morbidity and mortality. 30,31 Our primary health care system's limited functionality also impedes timely access to health facilities, as does indiscriminate access to prescription drugs in chemist stores, supermarkets, and sometimes from hawkers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation